A novel power amplifier structure for RFID tag applications - 邓见保 张世林 李德 张艳征 毛陆虹 谢生 (Journal of semiconductors, 2011)
A novel matching method between the power amplifier （PA） and antenna of an active or semi-active RFID tag is presented. A PCB dipole antenna is used as the resonance inductor of a differential power amplifier. The total PA chip area is reduced greatly to only 240 × 70 μm^2 in a 0.18μm CMOS process due to saving two on-chip integrated inductors. Operating in class AB with a 1.8 V supply voltage and 2.45 GHz input signal, the PA shows a measured output power of 8 dBm at the 1 dB compression point.